Efek Pendoping Nd3+ Pada Senyawa BaBi2-xNdxNb2O9 Terhadap Struktur, Sifat Dielektrik Dan Optik - Zulhadjri, Zulhadjri; Hermansyah, Tommy; Septiani, Upita (Jurnal Riset Kimia, 2024)
The Aurivillius compound with formula BaBi2-xNdxNb2O9 (x = 0.05, 0.1, 0.2, and 0.4) has been successfully synthesized using the molten salt method, showing potential as a ferroelectric material. The impact of Nd3+ substitution on the structure, morphology, dielectric, and optical properties has been systematically analyzed. XRD data refinement confirms that BaBi2-xNdxNb2O9 (BBNN) exhibits an orthorhombic structure with an A21am space group. Anisotropic plate-like grains were observed across all samples, decreasing their size as Nd3+ content increases. The ferroelectric transition temperature (Tc) decreases due to structural distortion caused by the reduction of the lone pair 6s2 electron effect of Bi3+ when substituted with Nd3+. Moreover, this structural distortion also contributes to an increase in bandgap energy (Eg). The diffuse ferroelectric phase transition is characterized by a broadened Tc peak induced by Nd3+ substitution due to increased cationic disruption in the bismuth layers. The ferroelectric phase with a lower and broader Tc suggests that the x = 0.4 sample has the potential for electrocaloric applications.